2008
DOI: 10.1007/bf03346419
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin analogs and gallstones: A retrospective survey on a large series of acromegalic patients

Abstract: GS are a frequent occurrence in acromegalic patients treated with SA, may occur at any time, but are seldom symptomatic or prompt acute surgery. Obesity and dyslipidemia appear to play a major role in the occurrence of GS in acromegalic patients on SA treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 58 publications
3
38
0
1
Order By: Relevance
“…Independently of the type of pituitary adenoma, a strong association was found between SSA therapy and the devel-opment of gallstones (confirming the literature data [23]) and kidney stones. Several mechanisms for which SSA contribute to gallstones formation have been postulated, leading to increased bile concentration and lithogenic changes in its composition, together with physical conditions favoring micro-crystal precipitation and stone for-mation.…”
Section: Discussionsupporting
confidence: 84%
“…Independently of the type of pituitary adenoma, a strong association was found between SSA therapy and the devel-opment of gallstones (confirming the literature data [23]) and kidney stones. Several mechanisms for which SSA contribute to gallstones formation have been postulated, leading to increased bile concentration and lithogenic changes in its composition, together with physical conditions favoring micro-crystal precipitation and stone for-mation.…”
Section: Discussionsupporting
confidence: 84%
“…15 Gallstones are commonly associated with somatostatin analogue treatment but are rarely symptomatic or require surgery. 15,25 In this study, 20% (n=15; 10mg) and 45% (n=34; 30mg) of patients had cholelithiasis; four patients underwent cholecystectomy. Gallbladder ultrasound is advised at regular intervals during pasireotide treatment.…”
Section: Discussionmentioning
confidence: 65%
“…All hyperglycaemias were reversible and there was no symptomatic cholelithiasis in our study. However, a previous study demonstrated increased prevalence of gallstones in patients with acromegaly who were treated up to 18 years, indicating the potential risks of prolonging therapy . Three patients were suspected of hepatic or renal cyst infection during our study.…”
Section: Discussionmentioning
confidence: 66%